Gambaran Pengobatan Massal Filariasis ( Studi Di Desa Sababilah Kabupaten Barito Selatan Kalimantan Tengah ) - Supatmi Dewi; Lintang Dian Saraswati; M. Sakundarno Adi; Praba Ginandjar (Jurnal Kesehatan Masyarakat (Undip), 2017)
Filariasis Elimination program through MDA (Mass Drug Administration) filariasis is a major national priority in all filariasis endemic area. Sababilah is the spot check site which started MDA in 2008. In 2014, Transmission Assessment Survey showed Mf rate Sababilah village of 1,7%. As a result, MDA failed and Sababilah village must add MDA filariasis 2 years which is the last round has been done in 2016. This study aimed to describe the filariasis mass treatment of endemic areas in Sababilah village. The research was descriptive with cross sectional approach. The data were collected using structured questionnaires as an instrument,observations, and Transmission Assessment Survey. Total sample of 107 respondents obtained by using cluster random sampling method as sampling technique.the data was analyzed using univariate frequency distribution table with narration. The result showed that 100% amicrofilaria,0% mf rate filariasis with non endemic area category, 78,5% respondent with good knowledge about filariasis,96% medicine practice, 99,1% respondent who received support from Ministrant personel of elimination, Further, required refresher and filariasis training for Minister Personel of Elimination, monitoring of patient in the period of selective treatment, Transmission Assessment Survey as follow up and improve the administration and data report of MDA filariasis.